Assessment of Nicotine Dependence among Adult Tobacco Users in Selected Urban Population of Ahmedabad City - Mall, Anjali; Vyas, Sheetal (National Journal of Community Medicine, 2020)
Background: Tobacco consumption is considered as a major public health problem in India. However, nicotine dependency is an area which has not been given much importance. The FTND score is considered as an easy tool to assess the dependence through physiological and behavioural symptoms. Aim and Objectives: To assess the nicotine dependence of the tobacco users in urban slums of Ahmedabad city. Methodology: Nicotine dependence among tobacco users (18-60 years) was studied by means of six -item. (Fagerstrom Test for Nicotine Dependence) in a community based interventional cluster randomized trial which was conducted through house to house survey from 20 clusters (slums) of Ahmedabad district. Result: Among 1968 people surveyed, a total of 400 subjects in intervention and control arm were interviewed. The prevalence of tobacco use was 20.3%. 23 % of the tobacco users had high to very high dependence. The overall FTND score was 4.5 and score for smoking was high 5.4 (2.2). Conclusion: A medium level of dependence was observed among the tobacco users in the current study. Tobacco intervention study can be more effective and productive if a baseline assessment of nicotine dependence is measured before any intervention.